Interactive educational software for dynamic systems control - Lima, José (2010)
This paper describes a tool for interactive learning that can be used as a teaching aid in control systems theory. It can be used by students for problem solving and individual learning. It can also be a powerful tool for speeding up the development cycle for robot control systems. As there is no need to do any special programming or debugging, the students can focus on the control items. The developed system is ready to use and allows testing different control methods. Usually, in control theory classes, students face a system defined only as a mathematical equation. The developed application allows them to control a realistic system with almost real world dynamics. A friendly appearance based on 3D graphics captivates the student's attention and gives instant feedback on the controller performance. As a case study, an inverted pendulum is controlled while placed on an omnidirectional vehicle. The inverted pendulum poses a classical control problem, a nonlinear and unstable system, typical of a large number of devices such as Segway Human Transporter and Rocket navigation. Omnidirectional vehicles allow movements in every direction and they are widely used in robotics soccer where the extra mobility is an important advantage.